Layer-by-Layer Assembly of PEDOT:PSS and WO3 Nanoparticles: Enhanced Electrochromic Coloration Efficiency and Mechanism Studies by Scanning Electrochemical Microscopy. (20th August 2015) - Ling, Han; Liu, Liang; Lee, Pooi See; Mandler, Daniel; Lu, Xuehong
Graphical abstract: Remarkably enhanced coloration efficiency is achieved in PEDOT:PSS/WO3 -NPs LBL hybrid films compared with single component LBL films, owing to the efficient charge transfer process studied through probing the conductivity change of PEDOT:PSS, WO3 -NP and hybrid films in redox switching process by scanning electrochemical microscopy. Abstract: Layer-by-layer assembly method is employed to fabricate multilayer hybrid films based on poly(styrenesulfonate)-doped poly(3, 4-ethylenedioxythiophene) (PEDOT:PSS) and tungsten oxide nanoparticles (WO3 NPs). Polyethylenimine (PEI) is deposited in between to introduce electrostatic force between the components. In the hybrid films, randomly oriented disk-like WO3 NPs are homogeneously distributed in the polymers and form an interdigitated structure. This very rough surface morphology hinders the formation of a continuous PEI layer between the electrochromic layers. Owing to the efficient charge transfer between the two active components and complementary electrical conductivity of the two components in the redox switching process, the coloration efficiency of the hybrid film is significantly improved to 117.7 cm 2 /C at wavelength of 633 nm. The underlying mechanism for the enhancement is verified by scanning electrochemical microscopic studies through probing the conductivity changes of PEDOT:PSS, WO3 -NP and hybrid films under various applied potentials.